Observed universal continuum morphology of raindrops reveals a concise diagram of heavy precipitation microphysics - Long Wen; Gang Chen; Shuguang Wang; Ji Nie; Kun Zhao (Proceedings of the National Academy of Sciences, 2026)
Persistent knowledge gaps in precipitation microphysics, particularly the nonlinear coupling between microphysical process hierarchies and raindrop size distribution (DSD) variability, keep introducing systemic uncertainties into precipitation retrievals and model simulations. Here, we address this challenge through a unified framework that integrates observations from China’s national-scale disdrometer network (1,031 sites) and 10-year global dual-frequency precipitation satellite dataset. First, a region-independent DSD continuum characterized by a universal linear relationship between raindrop diameter and concentration across diverse climatic zones is identified, extending and refining the conventional maritime-like and continental-like category. Then, we quantify the vertical stratification of microphysical processes in shaping and shifting this continuum. Implementations of our findings to reduce biases in current microphysics parameterizations are proposed and discussed. This study advances our fundamental understanding of the apparent heterogeneity yet inherent homogeneity in the microphysics of heavy precipitation, providing mechanistic insights to improve the performance of weather and climate models.